1992
DOI: 10.2135/cropsci1992.0011183x003200030010x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Location of Wheat Quantitative Trait Loci Affecting Agronomic Performance of Seven Traits, Using Reciprocal Chromosome Substitutions

Abstract: A major limitation to the genetic improvement of wheat (Triticum aestivum L.) is the lack of information about quantitative trait loci (QTLs). The objective of this study was to determine the chromosomal locations of QTLs controlling grain yield and yield components, grain test weight, plant height, and anthesis date. Reciprocal sets of chromosome substitution lines in duplicate between two hard red winter wheat cultivars, Cheyenne (CNN) and Wichita (WI), were used to identify the chromosomes bearing QTLs. Fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 0 publications
2
44
0
Order By: Relevance
“…To do this Berke et al (1992a) evaluated the reciprocal chromosome lines in the major ecological zones of Nebraska (Peterson 1992). Because the lines were developed by backcrossing, each substitution line was made in duplicate with the understanding that any random effect due to backcrossing of importance could be measured by comparing the duplicate lines for the same substitution.…”
Section: Identifying the Chromosomes Of Interestmentioning
confidence: 99%
See 2 more Smart Citations
“…To do this Berke et al (1992a) evaluated the reciprocal chromosome lines in the major ecological zones of Nebraska (Peterson 1992). Because the lines were developed by backcrossing, each substitution line was made in duplicate with the understanding that any random effect due to backcrossing of importance could be measured by comparing the duplicate lines for the same substitution.…”
Section: Identifying the Chromosomes Of Interestmentioning
confidence: 99%
“…Their similarity was later confirmed using DArT markers by Dr. Rustgi. Hence, though there were 21 chromosome substitution lines for each background (21 for CNN and 21 for WI), Berke et al (1992a), actually evaluated 84 + substitution lines due to some were at different levels of backcrossing, and most were BC 6 . In this research, chromosomes 3A and 6A were found to be the two most important chromosomes affecting grain yield.…”
Section: Identifying the Chromosomes Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of QTLs in wheat has a long history and is based on the use of morphological markers with cytogenetically derived single chromosome substitution lines (Berke et al 1992;Law 1966Law , 1967Law et al 1978;Snape et al 1985). However, QTLs can only be located onto individual chromosomes using this method, while the employment of molecular markers enables the researcher to map QTLs to specific chromosomal regions.…”
Section: Comparison With Ab-qtl and Other Qtl Analyses In Wheatmentioning
confidence: 99%
“…For many of the substitutions into Chinese Spring, such as Hope, for example, either five or six backcrosses were used (Kuspira & Unrau, 1957). The reciprocal substitutions of Cheyenne and Wichita underwent six to seven backcrosses (Berke et al, 1992). The substitutions of Bezostaya 1 into CappelleDesprez, mentioned later, have each undergone eight backcrosses.…”
Section: Background Effectsmentioning
confidence: 99%